Litlinks : activities for connected learning in elementary classrooms - Beeghly, Dena.; Prudhoe, Catherine ([S.l.] : McGraw-Hill Humanities/Social Sciences/Languages, 2001)
Litlinks: Activities for Connected Learning in Elementary Classrooms is designed as a supplemental text in children's literature, reading and language arts courses. The first chapters introduce using literature in the classroom. Chapters 4-7 provide examples of activities that connect literature sections with different content areas in the elementary curriculum. The activities are all linked to appropriate national standards.